The feasibility of bitscope raspberry pi for monitoring voltage and capturing data - Hasan Ba-Btain, Faisal Abdulkarem (2022)
A Raspberry Pi seems like a small open-circuit board in today's world, when computers are increasing more effective and advanced, it was created to provide a low-cost computer to every learner. Bitscope is a gadget with a high sampling rate and a high resolution, and the analog signal was converted to digital using a high-speed ADC. An oscilloscope is an electronic test instrument also an oscilloscope shows waveforms on some form of display. The oscilloscope has no storage memory, only shows the analyzed signal in real-time, the users capture the waveform manually, and it must store in a suitable place because of its size and weight. The method used in this project is to propose software that is fully user programmable -based oscilloscopes. To determine the Bitscope functionality a basic ohm’s law circuit is constructed to test the voltage output waveform and the output voltage waveform can be obtained on the Bitscope DSO. The results demonstrated proved that the prototype of the proposed measurement tool called (Digital Storage Oscilloscope) DSO which can display cursors performs and reports waveform measurements and adjusts voltage scale the vertical size of the waveform and that is fully user programmable -based oscilloscopes. These two portable devices allow users to be design software architecture, monitor and analyze voltage waveforms and capture data.